Gambaran Kejadian Ikutan Pasca Imunisasi (KIPI) Setelah Melakukan Vaksinasi Covid-19 Pada Masyarakat Banjarmasin Selatan - Darini Kurniawati; Iwan Yuwindry; Sariyasih Sariyasih (LPPM Universitas Sari Mulia, 2022)
ABSTRACT Background : Covid-19 attacks the respiratory tract which first appeared in December 2019 in Wuhan City, Hubei Province, China. The World Health Organization (WHO) has declared it as a global pandemic since March 11, 2020. The COVID-19 vaccination program in Indonesia has started on January 13, 2021. Covid-19 vaccination can cause Post Immunization Adverse Events (AEFI) which can be characterized by mild to moderate symptoms. heavy. Objective : To find how to follow-up events after immunization (KIPI) in the people of southern Banjarmasin after the Covid-19 vaccination. Methods : This research is an observational quantitative research with descriptive research type, this research only describes an object of research, then the research data obtained in the form of numbers will be qualitatively obtained so that the results obtained can be described. This research was conducted using the naranjo algorithm which was distributed to the public and input via Google Form. Results : This study shows that 37 respondents with a percentage of men 51% and women 49% obtained a score of 4-8, namely